Sens bycia dzieckiem (Mt 18,1-4) - Malina, Artur (Verbum Vitae, 2013)
Jesus’ answer to the question of the disciples about the hierarchy in the kingdom of heaven concerns the issue of fundamental importance for the understanding of their relationship to God. The Lord asserts that the issue more important than hierarchy is the condition for entering this kingdom. The attitude of little children towards their father and their dependence on him should be imitated by the disciples. They are encouraged to have trust in God, their Father, and to experience His paternal love. This way they can also build the proper relationship with their neighbors.